2021
DOI: 10.3390/ijerph18158213
|View full text |Cite
|
Sign up to set email alerts
|

The Health Behaviour of German Outpatient Caregivers in Relation to the COVID-19 Pandemic: A Mixed-Methods Study

Abstract: The COVID-19 pandemic has affected outpatient caregivers in a particular way. While the German population becomes increasingly older, the number of people in need of care has also increased. The health and, thus, the health behaviour of employees in the outpatient care become relevant to maintain working capacity and performance in the long term. The aims of the study were (1) to examine the health behaviour and (2) to explore pandemic-related perceived change of health behaviour among outpatient caregivers du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 175 publications
(260 reference statements)
1
11
0
Order By: Relevance
“…Similarly, physical activity had not decreased due to the COVID-19 pandemic according to a German panel survey [60]. However, a systematic review reports decreased physical activity during the COVID-19 pandemic lockdown [61], which is also consistent with the findings of the mixed-methods study among outpatient caregivers [40]. Although there are no cut-off values for the PSS-10 since it is not a diagnostic instrument [57], the average score may be considered a moderate stress perception when compared to mean values of the general US population [58,62].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Similarly, physical activity had not decreased due to the COVID-19 pandemic according to a German panel survey [60]. However, a systematic review reports decreased physical activity during the COVID-19 pandemic lockdown [61], which is also consistent with the findings of the mixed-methods study among outpatient caregivers [40]. Although there are no cut-off values for the PSS-10 since it is not a diagnostic instrument [57], the average score may be considered a moderate stress perception when compared to mean values of the general US population [58,62].…”
Section: Discussionsupporting
confidence: 70%
“…The MEDAS score as a measurement for overall dietary quality revealed slightly lower values compared to the general Italian population during the COVID-19 lockdown [59], although a generally higher adherence to the Mediterranean diet could be expected in their sample due to the geographical location and cultural aspects. In agreement with these results, a mixed-methods study from the COVID-19 context, outpatient caregivers in Germany showed unchanged or slightly deteriorating eating behaviour [40]. Similarly, physical activity had not decreased due to the COVID-19 pandemic according to a German panel survey [60].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations